Discussion contents during a lesson study conducted with knowledgeable others - Oben Kanbolat; Selahattin Arslan (Journal of Pedagogical Research, 2023)
Over the past two centuries, lesson study has been applied in different countries with different participant profiles. Lesson study is defined as a dynamic research-learning cycle of planning, applying, observing, and analyzing a lesson. Although the participants' discussions in lesson study practices were examined from different perspectives, they have not been analyzed in depth in terms of their contributions to teachers' and preservice teachers' professional development. In this study, the content and frequency of participants' discussions are examined. Six weeks of research were conducted by an academician, a teacher, and three mathematics pre-service teachers. The data were collected through field notes, video recordings, interviews, and focus group interviews. A total of eleven major headings were identified in the lesson study, concerning pedagogical and mathematical issues. The study also concluded that while classroom management was the most widely discussed topic, group and individual instructional techniques received less attention.